DEVELOPMENT OF STUDENT ECOPRENEURSHIP POTENTIAL THROUGH LEARNING BASED PROJECTS MODEL IN SOCIAL STUDIES LEARNING (Classroom Action Research in Class VII-A MTs Ar-Rohmah Bandung) - Rahayu, Sri (International Journal Pedagogy of Social Studies, 2017)
Abstract-This research related to the development of the potential of ecopreneurship students through project-based learning. The purposeof this research is caused by unrest demonstrated by students either in the process of learning which is very flat as well as assessment of the student's active role in the learning or suggested the practice as a form of character development. Researchers take a character-based entrepreneurial environment because the research location close to traditional and modern market. Problem formulated which examined is, related how the design, implementation, as well as the obstacles that occur in this research. The research method used is the classroom action research method using designs from Lewin according to Elliot. The design research of Lewin according to Elliot in each cycle begins with planning, action, observation, and reflection. Data collection techniques used are observation, field note, and documentation study. The instrument used is the observation sheet and rubric. Based on the research that has been done shows that project-based learning model can be an alternative model which could develop the potential of ecopreneurship grade VII-A MTS. Ar-Rohmah Bandung. This can be seen from the increase in the indicators of research after two cycles with a total of eight actions. The increase occurred on the indicators create, explore, creative, innovative, and confident. The results of this research can be an alternative to developing the social studies study that allows students to explore his creativity by doing a practice jump, so that learning becomes more meaningful for teachers as a student or as a character-forming the subject of the creation of the character.Keywords: project-based learning, the potential ecoprenership.